Procoagulant Activity of Thrombosthenln Preparations - Muszbek, L.; Fésüs, L.; Szabó, T.; Harsfalyi, J. (Thrombosis and Haemostasis, 1977)
3 x precipitated bovine thrombosthenin preparation exerted a powerful pro-coagulant effect similar to platelet factor 3 activity. In the presence of thrombosthenin the recalcification time, the kaolin clotting time and the Stypven tine considerably shortened, the partial thromboplastin time only slightly altered and the activated partial thromboplastin time did not change at all. Thrombosthenin highly accelerated the generation of intrinsic thromboplastin but it was not active in a factor IXa generation test. It neither possessed tissue factor like property nor influenced the activity of tissue factor preparation or the action of thrombin on purified fibrinogen. Thrombosthenin contained 109 μg phospholipid/mg protein, the composition of which was quantitatively determined by thin layer chromatography. The procoagulant activity as well as the phospholipid content were retained after agarose gel filtration. It is suggested that thrombosthenin having an associated phospholipid component significantly contributes to the clot promoting effect of activated platalets.